2023
DOI: 10.3389/fnut.2023.1220016
|View full text |Cite
|
Sign up to set email alerts
|

Greater adherence to the Dietary Guidelines for Americans is associated with lower diet-related greenhouse gas emissions but higher costs

Abstract: IntroductionFew studies have evaluated the sustainability of popular diet patterns in the US, which limits policy action and impedes consumer efficacy to make sustainable dietary changes. This study filled this gap by evaluating the relationship between diet quality, greenhouse gas emissions (GHGE), and diet cost for plant-based, restricted carbohydrate, low grain, low fat, and time restricted diet patterns.MethodsDietary data were retrieved from the National Health and Nutrition Examination Survey (2011–2018,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…We found that, in this nationally-representative survey of adults living in the US, improved dietary quality across the three dietary indices we examined was associated with lower GHGE. The inverse relationship between dietary quality and lower diet-related GHGE is consistent with several recent studies published in the US [ 12 , 17 ]. Another NHANES study found that vegan, vegetarian, and pescetarian diets had higher dietary quality and lower diet-related GHGE than omnivorous, keto, or paleo diets [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that, in this nationally-representative survey of adults living in the US, improved dietary quality across the three dietary indices we examined was associated with lower GHGE. The inverse relationship between dietary quality and lower diet-related GHGE is consistent with several recent studies published in the US [ 12 , 17 ]. Another NHANES study found that vegan, vegetarian, and pescetarian diets had higher dietary quality and lower diet-related GHGE than omnivorous, keto, or paleo diets [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous research in the US has consistently found that healthy plant-based diets are associated with lower diet-related GHGE, while unhealthy plant-based diets do not necessarily have the same environmental benefits [ 12 14 ]. In this context, the PHDI can fill an important gap, as it is a novel a priori measure that considers both environmental sustainability and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The FCID has been linked to several types of computational models that have been used to evaluate the environmental impacts of dietary intake. The FCID has been linked to data from life cycle analysis (LCA) [ 13 , 32 , 75 , 86 ] to evaluate the association between dietary intake and greenhouse gas emissions [ 13 , 19 , 21 , [31] , [32] , [33] , 75 , [86] , [87] , [88] , [89] , [90] , [91] ], energy use [ 13 ], water use and scarcity [ 32 , 86 , 90 , 91 ], and land use [ 86 , 90 , 91 ]. Greenhouse gas emissions have also been evaluated using carbon accounting methods [ 92 ].…”
Section: A Missing Ingredient To Promote Diet Sustainability Analyses...mentioning
confidence: 99%
“…Given its versatility, prior studies have used the FCID to evaluate the environmental impacts of individual foods or food groups [ 13 , 20 , 21 , 30 , 32 , 86 , 88 , 90 , 91 ] as well as diet patterns, including actual [ 19 , 31 , 88 ] and modeled [ 87 ] diet patterns. These also include diet patterns differentiated by diet quality [ 19 , 20 , 30 , 31 , 33 , 88 ] or other characteristics such as meat intake [ 87 ], as well as counterfactual scenarios such as adherence to dietary recommendations [ 90 , 93 ] or food substitutions [ 33 ]. Others have used the FCID to evaluate the environmental impacts of food loss and waste [ 13 , [19] , [20] , [21] , 30 , 87 , 88 ] as well as the impacts associated with demographic and behavioral characteristics [ 21 , 86 , [89] , [90] , [91] , [92] ].…”
Section: A Missing Ingredient To Promote Diet Sustainability Analyses...mentioning
confidence: 99%
See 1 more Smart Citation